Dossier aids. - Peeters, Andre; Van den Eynde, Hilde; Van Dooren, Pieter (Groot-Bijgaarden : De Standaard, 1995)
Fonds Suzan Daniel (FSD)
Bijlage bij De Standaard (1995) 27 november
Nederlands
Monografie
Keywords: aids